The Use of a Sequential Extraction Technique to Characterize Soil Trace Evidence Recovered from a Spade in a Murder Case in Brazil*. Issue 6 (24th June 2020) - Testoni, Samara Alves; Melo, Vander Freitas; Anne Dawson, Lorna; Malakoski, Joice; Cunico, Edimar; Junqueira Neto, Jorge Andrade
Abstract: Soil trace evidence can be useful in criminal investigations. A homicide which had occurred in South Brazil been concluded through the courts with a guilty conviction. A spade with soil traces adhering to it was seized from the confessed killer's house, it having been established that it had been used to bury parts of the victim's body. In the context of this confession, it provided an opportunity to test a protocol of analysis and verify the potential of discriminate soil sample analysis in such case works. This allowed us to test the practice of sequential analysis which had been developed for forensic case works in Brazil, with three sequential extractions: (i) 0.2 mol/L pH 3.0 ammonium oxalate; (ii) dithionite–citrate–bicarbonate; and (iii) 0.5 mol/L NaOH. It was possible to predict the sequence of events related to the homicide by using the sequential extraction technique and to conclude that: (i) the A horizon soil from the burial location of the torso was found to be very similar to the soil samples which had been recovered from the spade, which was able to be established despite there only being a small amount of soil adhering to the spade; (ii) the location where the legs were buried contributed a low amount of soil adhering to the spade. Therefore, it is suggested that, where possible, sequential extractions should be prioritized from a questioned sample to best provide information about the likely sequence of contact places and this test likely scenarios and criminal events.